2014
DOI: 10.1007/s13204-014-0325-2
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles for mercury determination in environmental water and vegetable samples

Abstract: Gold nanoparticles (AuNPs) capped with 2-mercapto succinic acid (MSA) were successfully applied for the determination of mercury in various water samples up to nanolevels without any interference. Alumina-coated MSA-capped AuNPs easily remove mercury species present in various samples. The absorbance spectrum was obtained at 547 nm. Other parameters like effect of pH, reagent concentration, interferences were studied. This method is simple, sensitive and successfully applied for the determination of mercury sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…The fluorescent responses showed that multivalent metal cations such as Fe 3+ and Cr 3+ might bind more strongly with Au NCs than monovalent metal cations. The results also showed the formation of an amalgam for Hg 2+ . EDTA was used as a chelating and competitive reagent, and the results showed that multivalent interaction was involved.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The fluorescent responses showed that multivalent metal cations such as Fe 3+ and Cr 3+ might bind more strongly with Au NCs than monovalent metal cations. The results also showed the formation of an amalgam for Hg 2+ . EDTA was used as a chelating and competitive reagent, and the results showed that multivalent interaction was involved.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, Au NCs facilitate the reduction of Hg 2+ via surface‐capped citrate. The amalgam formation also indicates citrate‐capped Au NCs . The QY of Au NCs is ~10 % ( n = 3).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations